2014
DOI: 10.1021/sb4001118
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of a Bacterial Microcompartment Targeting Peptide and Its Application in the Construction of an Ethanol Bioreactor

Abstract: Targeting of proteins to bacterial microcompartments (BMCs) is mediated by an 18-amino-acid peptide sequence. Herein, we report the solution structure of the N-terminal targeting peptide (P18) of PduP, the aldehyde dehydrogenase associated with the 1,2-propanediol utilization metabolosome from Citrobacter freundii. The solution structure reveals the peptide to have a well-defined helical conformation along its whole length. Saturation transfer difference and transferred NOE NMR has highlighted the observed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
256
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 175 publications
(264 citation statements)
references
References 48 publications
8
256
0
Order By: Relevance
“…Further investigation by NMR confirmed that the PduP N-terminal signal sequence adopts an ␣-helical conformation, providing support for this model of signal sequence-shell protein interaction (3). Only two signal sequences (both from natively encapsulated Pdu enzymes) have been identified and shown experimentally to localize proteins to the Pdu MCP, however, and a more diverse set of signal sequences with a variety of encapsulation levels is desirable for the encapsulation of heterologous pathways to allow tuning of the loading and stoichiometry of multiple heterologous enzymes in the Pdu MCP.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Further investigation by NMR confirmed that the PduP N-terminal signal sequence adopts an ␣-helical conformation, providing support for this model of signal sequence-shell protein interaction (3). Only two signal sequences (both from natively encapsulated Pdu enzymes) have been identified and shown experimentally to localize proteins to the Pdu MCP, however, and a more diverse set of signal sequences with a variety of encapsulation levels is desirable for the encapsulation of heterologous pathways to allow tuning of the loading and stoichiometry of multiple heterologous enzymes in the Pdu MCP.…”
mentioning
confidence: 63%
“…To observe Eut MCP formation, we used a fluorescent reporter of encapsulation in which EutC 1-20 is fused to GFP followed by a C-terminal ssrA tag, which mediates degradation of the fluorophore by the ClpXP protease in the cytosol (encapsulation in an MCP thus rescues the reporter from proteolysis). When expression of the encapsulation reporter construct pBADeutC [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] -gfp-ssrA was induced by the addition of 0.02% arabinose, fluorescent puncta were not observed in a ⌬eutR::FRT strain upon the addition of 30 mM ethanolamine and 150 nM vitamin B 12 , but puncta were observed in the ⌬pocR::FRT strain under the same conditions (Figs. 2 and 3).…”
Section: S Enterica ⌬Eutr::frt Does Not Form Eut Mcps But Can Form Pdumentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, MCPs provide natural starting points for applications aimed at organizing metabolic processes (Kim and Tullman‐Ercek, 2013; Lawrence et al ., 2014). They are especially attractive for applications where limited molecular exchange between different subcellular regions is desirable, either to improve channelling of substrates through multiple enzymatic reactions, or to limit the escape of toxic metabolites or even toxic proteins (Yung et al ., 2017).…”
mentioning
confidence: 99%